Pengembangan Aplikasi Pengolahan Data Sampah Kabupaten Sumbawa Berbasis Android - Mhd Alwi Syaputra Pulungan; Shinta Esabella (Himpunan Dosen Gemilang Indonesia (HDGI), 2024)
The rapid development of information technology has become an important part of everyday life and the public sector. The Environmental Service of Sumbawa City, NTB, faces challenges in processing waste data, requiring report printing features and hosting. This research aims to develop an Android-based Waste Data Processing Application. Development begins with improving the Back End of the previous Web Application, followed by the construction of an Android-based Front End, and integration using the Application Programming Interface (API). In this study using Qualitative methods and software development using Extreme Programming (XP) Method with Unified Modeling Language (UML) modeling, laravel and flutter frameworks, dart programming language and testing using blackbox tetsting. It is expected that the results of this study provide a solution for monitoring and evaluating the cleanliness of the Sumbawa Regency environment through Android-based digital media.